Lithium-ion cell balancing using auxiliary battery and DC-DC CUK converter - Rabah, Alzuhairi Mustafa (2022)
The lithium-ion battery became more popular to use due to its prominent characteristics such as energy density, power density and high terminal voltage of a single cell. However, if there is power regulation issue during the charging and discharging processes, the performance of the battery will be affected. In this case, the life of the battery will considerably reduce, which may result in undesirable outcomes such as fire or explosion. In order to avoid these issues, Battery Management Systems (BMS) is used to provide proper power regulation. BMS includes substantial subsystems such as SOC estimation, thermal management and cell balancing. This research concentrates on the cell balancing mechanism, which is an essential part of the BMS for extending battery life. The two basic types of cell balancing are passive cell balancing and active cell balancing. The active balancing topology utilized in this research is a Single Switch Capacitor (SSC), capacitor base, in order to perform module balancing and cell balancing inside internal modules. The BMS is based on the pack modularization architecture, where a single capacitor is fitted to transfer the energy from module to module to achieve balancing. While, the internal module balancing is accomplished with the use of a Single Switch Capacitor (SSC), Auxiliary Battery (AB) and Unidirectional DC-DC Cuk Converter (UCC) for boost charging. Finally, the BMS simulation is modelled using MATLAB/SIMULINK to validate the implementation system's results.